Changes in morbidity and medical care utilization after the recent economic crisis in the Republic of Korea - Kim Hanjoong; Chung Woo Jin; Song Young Jong; Kang Dae Ryong; Yi Jee Jeon; Nam Chung Mo (The World Health Organization, 2003)
OBJECTIVE: To examine and quantify the impact of the recent economic crisis on morbidity and medical care utilization in the Republic of Korea. METHODS: 22 675 people from 6791 households and 43 682 people from 12 283 households were questioned for two nationwide surveys that took place in 1995 and 1998, respectively. A separate sample pretest-posttest design was used and we conducted c2 test and logistic regression analysis after controlling for the maturation effect of the morbidity and medical care utilization. FINDINGS: The morbidity rates of chronic disease and acute disease increased significantly by 27.1% and 9.5%, respectively, whereas the utilization rates of outpatient and inpatient services decreased by 15.1% and 5.2%, respectively. In particular, the pace of decline in the utilization rate of outpatient services varied depending on the type of disease: morbidity rates for mental and behavioural disorders were 13.7%; for cardiovascular disease, 7.1%; and for injury, 31.6%. CONCLUSION: After the Republic of Korean economic crisis, the morbidity and medical care utilization rates changed significantly but the degree of change depended on the type of disease or service. The time-dependent relationship between the national economy and the morbidity and medical care utilization rates needs to be further investigated.